(untitled) (International Journal of Engineering and Computer Science, 2015)
Mobile ad-hoc networks are infrastructure-less networks used for communication between two or more nodes without a common access point. It is a collection of nodes that is connected through a wireless medium forming changing topologies. In mobile ad-hoc networks all the nodes are mobile in nature and having limited battery charge. Continuous change in position of nodes in the network degrades the battery charge of the nodes therefore it is necessary to save the battery power of those nodes so that the network lifetime can be long lasting. Nodes are in network are working in the presence of limited energy then energy efficient routing is necessary for reducing energy consumption. In this paper we proposed energy efficient Aodv routing protocol in which Dijkstra algorithm is enhanced to improve the overall performance of the network. Existing systems are not capable of finding the shortest and energy based path among the nodes in the network if multiple nodes fail simultaneously. Performance parameters are Packet delivery ratio, Throughput, Energy consumption and routing overhead. The simulation is done using NS2 network simulator.